Effects of Vitrification on Immature and in vitro Matured, Denuded and Cumulus Compact Goat Oocytes and their Subsequent Fertilization - GN Purohit; H Meena; K Solanki (JRI, 2012)
Background: Vitrification has proven to be more effective than slow freezing methods to cryopreserve mammalian oocytes. The objectives of this study were to evaluate the effects of vitrification on immature and in vitro matured, denuded and cumulus compact goat oocytes and their subsequent fertilization. Methods: Oocytes were either cryopreserved as immature cumulus compact (IMCC) (n=98 Exp 1; 102 Exp 2) and immature denuded (IMDN) (n=127 Exp 1; 109 Exp 2) or were first matured in vitro for 28 h and then cryopreserved as mature cumulus compact (MCC) (n=109 Exp 1; 89 Exp 2) or mature denuded (MDN) (n=112 Exp 1; 110 Exp 2) oocytes in four groups. The vitrification solution comprised of Dulbecco’s phosphate buffered saline supplemented with 0.5% sucrose, 0.4% bovine serum albumin and 8 M propylene glycol. After 7 days of cryopreservation in liquid nitrogen, oocytes in all groups were evaluated for normal morphologic survival and in vitro maturation (Experiment 1) and fertilization in vitro using epididymal buck spermatozoa (Experiment 2). Results: The number of oocytes retaining normal morphology was significantly higher (p <0.05) for cumulus compact oocytes (IMCC: 94.12% vs. IMDN: 89.22%, experiment 1 and MCC: 87.80% vs. MDN: 82.17%, experiment 2) compared to the denuded oocytes. The in vitro maturation of oocytes was highest for non-vitrified control oocytes. The maturation of vitrified IMCC oocytes was significantly higher than IMDN and their fertilizability was higher than MCC and MDN oocytes. Conclusion: The results suggest that immature cumulus compact goat oocytes better tolerate cryopreservation stress by vitrification in terms of fertilization rate.
Keywords: Goat, In Vitro fertilization, In vitro maturation, Oocytes, Vitrification